Platelet Unresponsiveness to Collagen: Involvement of Glycoprotein Ia-IIa (α2β1 Integrin) Deficiency Associated with a Myeloproliferative Disorder - Handa, Makoto; Kawai, Yohko; Kamata, Tetuji; Koyama, Takushi; Nagai, Hirofumi; Ikeda, Yasuo; Watanabe, Kiyoaki (Thrombosis and Haemostasis, 1995)
We studied a 66-year-old man with a myeloproliferative disorder who presented with a prolonged bleeding time and marked thrombocytosis (platelet count, 3,890 × 109/1). There was no past history of a bleeding disorder. The patient had normal coagulation data. His platelets completely lacked collagen-induced platelet aggregation and adhesion, but showed normal responses to other agonists. All family members tested showed normal platelet aggregation with collagen.Analysis of 125I surface-labeled platelets by two-dimensional SDS gel electrophoresis disclosed absence of the spot corresponding to platelet membrane GPIa (α2) but no other significant deficiencies of major platelet glycoproteins i.e., GPIb, IIb-IIIa, and IV. Immunoisolation studies of the patient’s platelets indicated that neither anti-GPIa nor anti-GPIIa (β1) monoclonal antibody (mAb) isolated any surface membrane proteins corresponding to GPIa. GPVI, a putative collagen receptor, was immunoisolated from the platelets. Indirect immunofluorescence study using flow cytometry confirmed that the patient’s platelets were totally deficient in surface expression of the GPIa-IIa complex (α2β1, integrin). In contrast, phytohemoagglutinin-activated T-lymphocytes from the patient expressed normal concentrations of this complex.The data suggest that our patient had an acquired deficiency of the platelet GPIa-IIa complex, due to a myeloproliferative disorder, which might account for the absence of responsiveness of his platelet to collagen.